Effective Factors in Organizing Volunteers to Participate in the Management of Urban Crises in Tehran, Iran - Ahmad Soltani; Hamidreza Khankeh; Ali Nasiri (دانش پیشگیری و مدیریت بحران)
Background and objective Tehran, the capital of Iran, is prone to disasters, making it necessary to implement comprehensive preparedness plans. City managers need to optimize the participation of volunteers in order to effectively implement these plans. This study aims to identify the effective factors in organizing volunteers for potential crisis management in Tehran, Iran. Method This is qualitative study. The data were collected by the review of related texts and conducting semi-structured in-depth interviews with 23 experts including urban crisis managers and citizens of Tehran. The data from the interviews were analyzed using the content analysis method to extract the concepts. Results For optimum organization of volunteers in urban crisis management, four main themes and 17 sub-themes were extracted from 199 primary codes. The themes included: Culture building, planning, recruiting/organizing, and training. Conclusion Effective volunteering for urban crisis management in Tehran requires culturalization, proper planning and recruiting/organizing, and providing education to volunteers and managers by utilizing tools such as social media.